The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1101/gr.10.5.652
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nuclear Lamin A/C R482Q Mutation and Partial Lipodystrophy with Hyperinsulinemia, Dyslipidemia, Hypertension, and Diabetes

Abstract: Nuclear lamins A and C are encoded by LMNA and are present in terminally differentiated cells. Lamins participate in DNA replication, chromatin organization, arrangement of nuclear pores, nuclear growth, and anchorage of nuclear membranes. In several Canadian probands with partial lipodystrophy, since found to have a common ancestor, we identified a rare novel LMNA mutation, R482Q, that completely cosegregated with the partial lipodystrophy phenotype. We evaluated the relationship between quantitative metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 19 publications
3
73
0
4
Order By: Relevance
“…Because mutations in LMNA have been associated previously with diabetes 20 and dyslipidemia, 44 we examined the relationship of LMNA polymorphisms identified in the Amish with the metabolic syndrome and its component traits. For the quantitative traits associated with metabolic syndrome (ie, glucose, obesity, and lipid levels), we estimated mean trait levels according to LMNA genotypes, whereas for the qualitative traits (metabolic syndrome, T2DM, and abnormal glucose tolerance), we compared disease prevalence across genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mutations in LMNA have been associated previously with diabetes 20 and dyslipidemia, 44 we examined the relationship of LMNA polymorphisms identified in the Amish with the metabolic syndrome and its component traits. For the quantitative traits associated with metabolic syndrome (ie, glucose, obesity, and lipid levels), we estimated mean trait levels according to LMNA genotypes, whereas for the qualitative traits (metabolic syndrome, T2DM, and abnormal glucose tolerance), we compared disease prevalence across genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent positional candidate genes include APOA (apolipoprotein A2), 6 PBX1 (pre-B-cell leukemia transcription factor 1), 7 slc19a2 (solute carrier family 19 [thiamine transporter] member 2), 8 INSRR (insulin receptor-related receptor gene), 9 KCNJ9 and KCNJ10 (potassium inwardly-rectifying channel, subfamily J, members 9 and 10), 10 18,19 and LMNA (lamin A/C). 20 This region is approximately 160 to 180 cM from p-telomere and corresponds to a region of chromosome 1 that has been linked to T2DM in several other populations, including Pima Indians, 21 Utah Mormons, 22 British whites, 23 French whites, 24 and Chinese. 25 Familial partial lipodystrophy is a condition associated with severe insulin resistance, diabetes, dyslipidemia, and atherosclerosis, 26 making LMNA an excellent positional candidate gene for metabolic syndrome, T2DM, and related traits.…”
mentioning
confidence: 99%
“…In 50% of the FPLD families, there is a link between FPLD and the LMNA (lamin A) gene also associated with premature forms of aging, which codes for the nuclear envelope protein lamin A/C [130]. Different mutations in this gene have been identified as culprits for lipodystrophy, but the mechanism by which it occurs is not known [131][132][133]. Mutations in the LMNA gene are linked to a decrease in the plasma concentrations of adiponectin and leptin, and an increase in circulating TNF-α concentrations, which may cause the insulin resistance observed in FPLD patients [134].…”
Section: Lipodystrophymentioning
confidence: 99%
“…14 Careful phenotypic or "phenomic" studies performed in extended FPLD2 kindreds have shown metabolic changes that were similar to those seen in the common MetS. 15,16 In young adulthood, the characteristic biochemical profile seen in FPLD2 carriers of mutant LMNA included elevated plasma concentrations of free fatty acids, insulin and C-peptide, TG, and C-reactive protein (CRP), with depressed plasma concentrations of HDL cholesterol, leptin, and adiponectin. 15,16 Depressed adiponectin in particular could be a potent atherosclerosis risk factor in lipodystrophy syndromes.…”
Section: Fpld2: a Monogenic Form Of Metabolic Syndrome With Early Athmentioning
confidence: 99%
“…15,16 In young adulthood, the characteristic biochemical profile seen in FPLD2 carriers of mutant LMNA included elevated plasma concentrations of free fatty acids, insulin and C-peptide, TG, and C-reactive protein (CRP), with depressed plasma concentrations of HDL cholesterol, leptin, and adiponectin. 15,16 Depressed adiponectin in particular could be a potent atherosclerosis risk factor in lipodystrophy syndromes. Hypertension usually presents next, followed by T2DM that causes profound changes in the metabolic intermediate traits.…”
Section: Fpld2: a Monogenic Form Of Metabolic Syndrome With Early Athmentioning
confidence: 99%